FLOW CYTOMETRY DIAGNOSIS OF (CD4+/CD8+) T CELL LYMPHOBLASTIC LEUKEMIA ASSOCIATED WITH NORMAL KARYOTYPE - CASE REPORT - Trajkova, Sanja; Chevrevska, Lidija; Ivanovski, Martin; Dukovski, Dushko; Simjanovska-Popova, Marija; Panovska Stavridis, Irina (Radiance Research Academy, 2013)
Adult T-cell leukemia/lymphoma (ATLL) is a peripheral T-cell neoplasm caused by human T-cell lymphotropic virus type I (HTLV-I). The neoplastic cells are highly pleomorphic and are usually CD4+ and CD8- phenotypically, but some rare cases have unusual immmunophenotype presented by co-expression of CD4/CD8 double positive cells. We present a rare case of a patient with T cell lymphoblastic leukemia associated with double-positive (CD4+/CD8+) blast cells. The diagnose was accessed with multiparameter immunophenotyping by flow cytometry analyses of bone marrow, and for the first time in our country, we confirmed isolated relapse of double-positive (CD4+/CD8+) T cell lymphoblastic leukemia in CNS
Keywords: T-cell Acute Lymphoblastic Leukemia; flow cytometry; cerebrospinal fluid